Analisis Kebijakan Atasi Credit Crunch Bank Umum di Indonesia - Risna Kartika; Marlina Nur Lestari; Rina Madyasari (Universitas Indraprasta PGRI, 2022)
COVID-19 has been declared a pandemic by WHO on March 9, 2020 because the spread of Covid-19 has reached 118 countries, including Indonesia. This pandemic not only has an impact on the health crisis but also has an impact on the economic crisis, one of which is the banking financial sector. This is reflected in credit growth which tends to decline with the average credit growth of commercial banks only 0.09% from January 2020 to June 2021. The purpose of this study is to analyze policies to overcome the credit crunch at commercial banks in Indonesia. The method used in this study is a descriptive method with a literature review approach. Based on research, it is known that the policies that have been launched to reduce the credit crisis of Commercial Banks together with the recovery of economic recovery in Indonesia are countercyclical policies and integrated policies, both policies contain credit restructuring with long term loans, subsidies or reductions in interest rates, reduction of interest arrears as well as a reduction in arrears of principal and/or credit conversion and credit guarantees.The researcher recommends that the vaccination program must be realized immediately so that all communities can quickly obtain programs to encourage more optimal activities and the dissemination of health protocols for the prevention of Covid-19 needs to be continuously echoed so that they remain implemented, because these various policies cannot run optimally without the implementation of these programs.